Determination of Sex-Reversal Rate and Growth Performance in Diallel Hybrids of Nile Tilapia (Oreochromis niloticus) and Blue Tilapia (Oreochromis aureus) - Francis Oster NWACHI; Arnold Ebuka IRABOR (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
A total of 200 fish samples (100 Oreochromis niloticus (Nile tilapia) and 100 Oreochromis aureus (Blue tilapia)) were used for this research aimed to produce a population of tilapia species that is skewed toward the male population. Three mating periods were carried out in total. The males were removed from the hapa after each round of egg production to allow repercussion. Fries from the experimental units were collected, counted, and stocked in a tank with a dimension 3 x 1 x 4 m2 and were fed to satiation while maintaining the basic water quality. The sex ratio data were subjected to student t-test analysis, while that of growth parameters were examined by ANOVA on Spss version 25. Results obtained showed a true hybridization between Nile tilapia and Blue tilapia that produced offspring that skewed toward the male population. A male skewed population was produced through interspecific crossing of two related strains of tilapia. This pattern repeated itself throughout the times when mating pairing was initiated. At the end of the trials, the hybrids and their reciprocals produced a higher number of male fish compared to the female. Hybrid 1 produced 93% male, while hybrid 2 produced 71% male. Furthermore, better performance was recorded for the hybrids compared to their pure strain despite the lower feed intake. Conclusively, a male skewed population is best produced through interspecific crossing of two related strains of hybrid tilapia.